Peran Serikat Pekerja Federasi Serikat Pekerja Transport Indonesia (FSPTI) dalam Membela Hak-Hak Buruh Tenaga Kerja Bongkar Muat (TKBM) di Kota Padangsidimpuan - Marwan Busyro; Bandaharo Saifuddin (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study is entitled "The Role of the Indonesian Transport Workers Federation (FSPTI) in Defending the Rights of Stevedoring Workers (TKBM) in Padangsidimpuan City". The background of this study is based on the importance of the existence of trade unions as a forum for workers' struggle in protecting and fighting for the normative rights of workers as guaranteed in Law Number 21 of 2000 concerning Workers' Unions/Labor Unions. In practice, many workers still face employment problems due to their weak bargaining position, lack of legal awareness, and low protection from employers. The purpose of this study is to determine and analyze the role of the FSPTI of Padangsidimpuan City in defending the rights of Stevedoring Workers, as well as to assess the effectiveness of the implementation of Law Number 21 of 2000 on the implementation of trade union functions at the regional level. The research method used is empirical juridical, with a qualitative approach that combines primary data through interviews, as well as secondary data through literature reviews of laws and regulations and related legal literature. The research results indicate that the Padangsidimpuan FSPTI plays a strategic role in advancing the interests of TKBM workers through advocacy, legal assistance, and negotiations with employers and local governments. However, the implementation of Law Number 21 of 2000 has not been fully effective due to challenges such as limited resources, low participant participation, and weak enforcement of labor laws. Overall, the FSPTI has made maximum efforts to advocate for the rights of TKBM workers, but further government support and organizational capacity building are needed to further optimize the union's function.